Ethical complexities of responding to bystander risk in HIV prevention trials. (October 2019) - Eyal, Nir; Wikler, Daniel
Till Bärnighausen points out the medical risks that two categories of contemporary HIV prevention trials, for "treatment-as-prevention" and for "pre-exposure prophylaxis, " pose to people who are not study participants. Bärnighausen's compelling case forces reconsideration of the absence of bystanders in the law governing ethical review of health research. It raises the intriguing question: to what legal protection are bystanders morally entitled? The remedy might seem to be to accord bystanders the rights and protections currently accorded to human study participants. We counsel against that remedy on three grounds, inviting colleagues to suggest alternatives.